Origins of GA II: The End of Culture? - Gans, Eric Lawrence (2023)
The Origin of Language (TOOL), published in 1981 by the University of California Press, is the only one of my books that was promoted by the publisher; an advertisement with my picture even appeared in the New York Review of Books. Its failure to attain best-seller status reflects less a weakness in the theory than...